Bread Making Process from Banana Flour and Modified Cassava Flour in Silo Village, Jember - Aji Sukoco; Septy Handayani (Universitas Negeri Surabaya, 2023)
Cassava and banana are the most agricultural commodities grown in Silo Village. Farmers plant these commodities as a response to local needs. In order to add more value to these commodities, the team of community service program strives to make a gluten-low bread by utilizing flours made from cassava (mocaf) and banana. This community service program was implemented to introduce bread made from mocaf and banana flours as alternative flours for wheat flour, as well as enhance skills and knowledge of the society in Silo village. The methods used in this community service program were participants approach and field observation, training program, and accompaniment of participants. The monitoring program was conducted during accompaniment of participants to check the progress established in the development objective. Modules were also provided by the team of community service program. The group of the Family Welfare Movement in Silo Village were interested during the training program due to the innovation presented. The gluten-low bread was processed by supplementing mocaf and banana flour to the dough. A combination of 70% of wheat flour, 20% of mocaf, and 10% of banana flour resulted in airy and soft bread, as well as delicious taste. As a consequence of gluten reduction in the raw materials, the amount of instant yeast and the length time of dough fermentation were increased twice compared to the common bread made from whole wheat flour. About 30% of wheat flour in the bread-making process could be substituted by the combination of 20% of mocaf and 10% of banana flour. The community service program could also be performed to improve the experience and skills of the group of Family Welfare Movement in Silo Village.